Personality Disorders – a basic information review - Waloch, Kamil; Łepik, Michał; Uszok, Zofia; Rosiak, Krzysztof; Płeska, Kacper; Reguła, Kacper; Wojtania, Joanna; Piaszczyński, Szymon; Czajka, Andrzej; Szymański, Bartłomiej (Quality in Sport, 2024)
Personality disorders refer to a collection of mental health conditions defined by persistent deviations from societal norms in thoughts, behaviors, and emotions. These deviations frequently result in challenges in interpersonal relationships, self-perception, and overall functioning, potentially causing distress in various aspects of life. The DSM-5 classifies personality disorders into three clusters. Cluster A contains paranoid, schizoid and schizotypal personality disorders which are characterized by strange and eccentric behaviors. Cluster B contains narcissistic, histrionic and antisocial personality disorders which are characterized by dramatic and emotional behaviors. Cluster C contains avoidant, dependent and obsessive-compulsive personality disorders which are characterized by anxious and fearful behaviors.